2013
DOI: 10.1186/1471-2164-14-286
|View full text |Cite
|
Sign up to set email alerts
|

The Nocardia cyriacigeorgica GUH-2 genome shows ongoing adaptation of an environmental Actinobacteria to a pathogen’s lifestyle

Abstract: BackgroundNocardia cyriacigeorgica is recognized as one of the most prevalent etiological agents of human nocardiosis. Human exposure to these Actinobacteria stems from direct contact with contaminated environmental matrices. The full genome sequence of N. cyriacigeorgica strain GUH-2 was studied to infer major trends in its evolution, including the acquisition of novel genetic elements that could explain its ability to thrive in multiple habitats.ResultsN. cyriacigeorgica strain GUH-2 genome size is 6.19 Mb-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Intraspecies variation in susceptibility to imipenem has also been reported in N. cyriacigeorgica (Schlaberg et al, 2014). Recently, genomic sequencing of N. cyriacigeorgica (GUH-2 strain) revealed virulence determinants such as the production of superoxide dismutase and peptide synthesis probably for siderophore/toxin production (Zoropogui et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecies variation in susceptibility to imipenem has also been reported in N. cyriacigeorgica (Schlaberg et al, 2014). Recently, genomic sequencing of N. cyriacigeorgica (GUH-2 strain) revealed virulence determinants such as the production of superoxide dismutase and peptide synthesis probably for siderophore/toxin production (Zoropogui et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that modern molecular biology tools have improved diagnosis of this elusive pathogen and enabled finer species level identification, giving increased recognition to this well-established, rather than emerging, genus as an agent of infection. Conversely, information obtained from whole genome sequencing of at least one N. cyriacigeorgica genome suggests that this organism is on the path of an ongoing adaptation from an environmental bacterium to an emerging pathogen [52]. In either case, it is clear that accurate diagnosis and timely treatment of nocardial infections are crucial because undiagnosed and latent infections have the ability to spread from primary sites to more sensitive regions in the body that can be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the SH22a genome with the other three fully sequenced genomes of the genus Nocardia (N. farcinica IFM 10152 [31], Nocardia cyriacigeorgica GUH-2 [32], and Nocardia brasiliensis HUJEG-1 [33]) was carried out. These analyses revealed that in comparison to the predicted proteomes of the other Nocardia strains, many protein families of SH22a which might be involved in the degradation of xenobiotics, other hardly degradable compounds, and polymers are represented at higher percentages.…”
Section: Resultsmentioning
confidence: 99%